The implementation of PJBL-STEAM model on eleven graders’ creative thinking skills through jumputan batik pattern-making project of acid-base-related material - Aan Kartika Fitriani; Lina Mahardiani; Erwan Nugroho (Education and Development Research, 2025)
This mixed-method research aimed to analyze the influence of the PjBL-STEAM learning model on the creative thinking skills of grade XI students through a jumputan batik pattern-making project. The main problem was the demand for creative adaptation skills in the 21st century. By collecting data through product assessment observations, questionnaires, and interviews, this study found that the PjBL-STEAM model had a positive and strong impact, particularly in the aspects of fluency and flexibility, which reached 75.50%–78.00%. However, significant challenges were found in the aspects of originality and elaboration, with lower scores (52.27%–58.20%), indicating the need for further development on the innovation and detail of students' work. Overall, the PjBL-STEAM model is effective, but it requires more specific guidance to encourage the generation of unique and detailed ideas.